Kelet Terminal Planning Keling District – Jepara Regency According to Ministry of Transportation Standards (Science and Technology (SciTech), 2023)
Abstract - Basically, transportation is needed to facilitate all activities carried out by humans. The development of land transportation such as the development of public transportation is very rapid from year to year, this requires the development and progress of the terminal as one of the road transportation infrastructure for the purpose of loading and unloading people and or goods, as is the case in Kelet Terminal Kec. Keling Kab. Jepara is a type C passenger terminal, but along with the development of transportation, this terminal has changed its function to a type B terminal, so it is necessary to develop a terminal both in terms of capacity and infrastructure. The method used in this study is to record the number plates of public transport entering, parking and exiting the terminal. Before doing research, first ask for a research permit from the campus and the District Government. Jepara in this case BAPEDA Kab. Jepara. The position of Kelet Terminal on the existing road network system can be said to be quite strategic because it is on the main city route that connects Keling District with other areas, both in the western part of the city and with areas in the eastern part. Kelet Terminal has an area of 8,796 m², which consists of a building area and public transport parking area. Kelet Terminal currently has a parking area of 866 m² which is used by public transportation, microbuses, AKDP and motorcycles. Based on the results of calculations and survey results in the field, the need for parking spaces at the Kelet Terminal is currently unable to serve the existing needs, where many of the microbuses are waiting for passengers outside the terminal. As a form of solving the problems that exist in the Kelet Terminal is to develop the terminal by optimizing the existing market land that can be used for the development of the Kelet Terminal.   Keywords: Exhaust Terminal, Capacity, Transportation;